Profile of pregnant women with preeclampsia and its termination method - Vebianti Permadi; Aditiawarman Aditiawarman; Pudji Lestari (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Pregnancy with preeclampsia in this study was mostly terminated by cesarean section. A small percentage was with vaginal delivery.2. Most preeclamptic mothers gave birth by cesarean section exhibited severe symptoms of preeclampsia, such as severe hypertension, severe proteinuria, and visual impairment. ABSTRACT Objectives: To determine the symptoms of pregnant women with preeclampsia through the method of pregnancy termination. Materials and Methods: This study used a cross-sectional method for descriptive analysis. The total sample included 75 pregnant women with preeclampsia. The sampling techniques was carried out with purposive sampling. This study used auxiliary data in medical records of preeclampsia mothers who gave birth at Taman Husada Regional Hospital, Bontang, Indonesia, in 2019. Results: The results showed that most preeclampsia mothers delivered by cesarean section (CS). Among mothers who gave birth by cesarean section, there were severe symptoms of preeclampsia, 74.14% had severe hypertension with systolic blood pressure of > 160 mmHg or diastolic blood pressure of > 110 mmHg. Those with severe proteinuria with urine protein > 2g/24 hours or > +2 were 82.76% and 60.35% of those complained visual impairment with blurred vision. Conclusion: These data indicated that most mothers with preeclampsia gave birth by cesarean section and exhibited severe symptoms of preeclampsia.